Zmiany w dostępie do zasobów. Analiza przemian w poziomie i jakości życia Polaków = Changes in access to resources: analysing transformations of the level and quality of living of the Poles - Frątczak-Müller, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The purpose of this study is the analysis of changes in the quality of living of people during political transformation in Poland. It presents the dynamics of changes in access to resources as well as the conditions and social diversity of selected indicators of the quality of living. The empirical basis for the article is data collected in the framework of the research project on "The quality of living of Lubuskie region inhabitants" using a random test representative of the Lubuskie province.
Keywords: jakość życia; poziom życia; transformacja ustrojowa; województwo lubuskie